(untitled) (Perner’s Contacts, 2011)
The contribution brings an insight into the different forms of material procurement. It compares so-called traditional approach of procurement with Just-in-Time and Just-in-Sequence approaches and points out main characteristics of each system with respect to logistic and purchasing activities